(3JcedI TQM GdegPHs - (3Ydj Hf YHO GdcGaj Hf Ydj Hf JeGe GdSHcj GdCfUGQj GdNRQLj, CHh GdMSf, Jbqj GdOjf,J (B756 (3g` s; (3GdajQhRGHGOj GdTjQGRj , CHh ESMb EHQGgje Hf Ydj GdTjQGRj, CHh GSMGb , LeGd GdOjf,J (B476 (3g` s
(3ChdgG (B:s
(3bGd GdeUfa QMeg Gddg JYGdi HGH GdHjY GdeUQCg EPG ETJQi fGbI ChTGg eUQCg s
(3BNQgG (B:s
(3hde jPcQgG aj gPG GdegPH hPcQ GdeSFdg GdChdihMSHfG Gddg hfYe Gdhcjd s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdTGaYjs